Hypoxic Respiratory Chemoreflex Control in Young Trained Swimmers - Arce-Alvarez, Alexis; Veliz, Carlos; Vazquez-Munoz, Manuel; von Igel, Magdalena; Alvares, Cristian; Ramirez-Campillo, Rodrigo; Izquierdo, Mikel; Millet, Gregoire P.; Del Rio, Rodrigo; Andrade, David C. (My University, 2021)
During an apnea, changes in PaO2 activate peripheral chemoreceptors to increase respiratory drive. Athletes with continuous apnea, such as breath-hold divers, have shown a decrease in hypoxic ventilatory response (HVR), which could explain the long apnea times; however, this has not been studied in swimmers. We hypothesize that the long periods of voluntary apnea in swimmers is related to a decreased HVR. Therefore, we sought to determine the HVR and cardiovascular adjustments during a maximum voluntary apnea in young-trained swimmers. In fifteen trained swimmers and twenty-seven controls we studied minute ventilation (V-E), arterial saturation (SpO(2)), heart rate (HR), and autonomic response [through heart rate variability (HRV) analysis], during acute chemoreflex activation (five inhalations of pure N-2) and maximum voluntary apnea test. In apnea tests, the maximum voluntary apnea time and the end-apnea HR were higher in swimmers than in controls (p < 0.05), as well as a higher low frequency component of HRV (p < 0.05), than controls. Swimmers showed lower HVR than controls (p < 0.01) without differences in cardiac hypoxic response (CHR). We conclude that swimmers had a reduced HVR response and greater maximal voluntary apnea duration, probably due to decreased HVR.
Keywords: apnea; autonomic nervous system; chemosensitivity; hypoxia; swimming